2016
DOI: 10.1039/c5ra14951g
|View full text |Cite
|
Sign up to set email alerts
|

The hierarchies of hydrogen bonds in salts/cocrystals of isoniazid and its Schiff base – a case study

Abstract: A series of two salts of isoniazid and two cocrystals of its Schiff base have been synthesized and well characterized. Further, the hydrogen bonding patterns have been studied and the correlation between the bond distances and corresponding pKa's have been deduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Lemmerer et al synthesized various isoniazid derivatives by using different ketone modifiers and designed the corresponding cocrystals [27]. Oruganti et al designed different cocrystals using isoniazid and N -(propan-2-ylidene)-isonicotinohydrazide, a derivative of isoniazid [28]. In this study, N -(propan-2-ylidene)-isonicotinohydrazide, an isoniazid derivative, was synthesized and isolated through sonocrystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Lemmerer et al synthesized various isoniazid derivatives by using different ketone modifiers and designed the corresponding cocrystals [27]. Oruganti et al designed different cocrystals using isoniazid and N -(propan-2-ylidene)-isonicotinohydrazide, a derivative of isoniazid [28]. In this study, N -(propan-2-ylidene)-isonicotinohydrazide, an isoniazid derivative, was synthesized and isolated through sonocrystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the formation of these multicomponent crystals does not lead to changes in the nature of the API, unlike the situation observed during salt formation, where the API must or may be protonated [4]. Co-crystals containing heterocyclic nitrogen bases have been studied extensively, especially those with mono-and di-carboxylic acids as co-formers, and it can be concluded that the interaction between a carboxylic acid and a pyridine is a supramolecular synthon of frequent use in crystal engineering that may exist as a cocrystal (CO 2 H• • • N) or as salt (CO 2 − • • • HN + ) [5][6][7][8][9]. However, few studies are known of cocrystals with carboxylic acids as co-formers that also contain a hydroxyl moiety [10], such as the α-hydroxycarboxylic acids, particularly against isonicotinic acid hydrazide (isoniazid, inh) (Scheme 1) as API.…”
Section: Introductionmentioning
confidence: 99%
“…Trans-cinnamic acid derivatives have shown to augment the activity of various antibiotics against Mycobacterium avium [12] and also show antioxidant, anti-inflammatory and cytotoxic properties. [13] , [14] Cinnamic acid derivatives bearing phenolic hydroxyl groups also have free radical scavenging properties [15] , [16], and so may sacrificially reduce the chemical degradation of easily oxidized APIs, such as INH. Weakly basic drugs show decreased solubility and dissolution as pH increases from 1 to 7 along the gastrointestinal tract, which is detrimental to drug absorption.…”
Section: Introductionmentioning
confidence: 99%